Physiotherapy after Surgical Treatment in Osteomyelitis: A Systematic Review - Tushara Nair; G. P. Kumar (Research Highlights in Disease and Health Research Vol. 9, 2023)
Osteomyelitis is an inflammatory process caused by an infecting microorganism leading to bone destruction. Sequestrectomy, Saucerization, Curettage, and Excision of the infected bone are commonly used treatment procedures. Many case studies focusing on physiotherapy after the surgical treatment of osteomyelitis have been published till date. But there is no clear evidence on the basic line of treatment, so this review aims to analyze the various physiotherapy management protocols available after surgical treatment of Osteomyelitis. The electronic databases PUBMED, CINAHL, PEDRO, Cochrane Library, and Science Direct were searched for the last 10 years from 2012 to 2022. Seven case reports were included in this review. Different physiotherapy protocols used in these studies were identified and discussed. Thus, this review provides a brief overview of the common line of physiotherapy management used to decrease pain, improve the range of motion, muscle strength, and functional status of patients after the surgical management of osteomyelitis.